The Effect of Special Exercises According to Strength Reserves On Maximum Strength And Muscle EMG Of Weightlifters - Mahdi, Mustafa Salih; Abdul-Hassan, ghassan Adeeb (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research lies in types of strength and the differences between maximum strength and great strength. The problem of the research lies in describing this type of strength and how to train to develop it. The aim of the research was to identify the effect of special exercises according to strength reserve on weightlifters’ maximum strength. The researcher used the experimental method. The subjects were (6) weightlifters. He conducted maximum strength tests of arms and legs. The data was collected and treated using proper statistical operations. The researcher concluded that training according to strength reserves have a positive effect on maximum strength and muscle EMG The researcher recommended the necessity of defining the highest strength as one type of strength and differentiating it from maximum strength.